The Anticonvulsant Zonisamide Reduces Ethanol Self-Administration by Risky Drinkers - Sarid-Segal, Ofra (2009)
OBJECTIVE: The purpose of this study is to examine the effects of zonisamide on ethanol self-administration and subjective effects in risky drinkers using a human laboratory paradigm. METHOD: We conducted a double-blind, placebo-controlled study of the effects of zonisamide 100 mg on ethanol self-administration and urge to drink in risky drinkers (N = 10) (1). RESULT: During the second hour of a 2-hour self-administration session ethanol consumption was 50% lower in the zonisamide group as compared to the placebo group. Urge to drink was also significantly lower under the zonisamide condition. CONCLUSION: These results indicate that a single dose of zonisamide reduces urge to drink and the quantity of ethanol self-administered by risky drinkers during their second hour of access to alcohol. SCIENTIFIC SIGNIFICANCE: Zonisamide may help individuals drinking at risky levels reduce their intake of alcohol.